ISLAMIC EDUCATION MANAGEMENT IN SENIOR HIGH SCHOOL - Nurmalia Damanik; Yahfizham (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
In Islam, everything should not be done haphazardly. Everything must be regulated and carried out by the rules. Moreover, the education management process, all of which must be well designed. SMA/MA educational institutions are asked to provide quality education because inferior educational institutions will gradually be abandoned by society and automatically marginalized. The purpose of this article is to understand the implementation of Islamic education management in SMA/MA, and to study the development and improvement of the quality of personnel in the management of Islamic education in SMA/MA. This type of research was conducted using qualitative research because the data is presented through descriptive analysis. The data collection technique is a literature survey by looking for scientific articles published at least in 2018. Through this research it can be shown that the implementation of Islamic education management in SMA/MA is through programs such as providing well-packaged student orientation events, delivering student learning programs that are in accordance with the curriculum by adding religious values, and running and assisting the program. extracurricular activities that lead to the formation of maturity and morale of students through healthy physical and social activities. In order to maximize human resources, both school principals, teachers and related parties need to carry out coaching and further learning both at the local and international levels so that from this learning and coaching they are able to answer the challenges the industrial world is currently facing in the era of society.